A review of the demographic profile, symptomatology and management of patients suffering with HIV/AIDS at Port Shepstone Hospital, KwaZulu-Natal, South Africa - Campbell, Laura (Department of Public Health and Family Medicine, 2015)
Includes bibliographical references.